Immune Reactivity of a 20-mer Peptide Representing the Zika E Glycan Loop Involves the Antigenic Determinants E-152/156/158 - Etienne Frumence; Juliano G. Haddad; Bénédicte Vanwalscappel; Jessica Andries; Jason Decotter; Wildriss Viranaicken; Gilles Gadea; Philippe Desprès (Viruses, 2020)
Mosquito-borne Zika virus (ZIKV) causes a severe congenital syndrome and neurological disorders in humans. With the aim to develop a live-attenuated ZIKV strain, we generated a chimeric viral clone ZIKALIVax with African MR766-NIID strain as backbone and the envelope E protein of epidemic Brazilian BeH810915 strain. The MR766-NIID residues E-T152/I156/Y158 were introduced into BeH810915 E protein leading to a nonglycosylated ZIKALIVax. Recently, we reported that the residues E-152/156/158 that are part of ZIKV glycan loop (GL) region might have an impact on the availability of neutralizing antibody epitopes on ZIKV surface. In the present study, we evaluated the antigenic reactivity of a synthetic 20-mer peptide representing the ZIKALIVax GL region. The GL-related peptide was effective for the detection of GL-reactive antibody in mouse anti-ZIKALIVax immune serum. We showed that the residue E-158 influences the antigenic reactivity of GL-related peptide. The ZIKALIVax peptide was effective in generating mouse antibodies with reactivity against a recombinant E domain I that encompasses the GL region. The GL peptide-reactive antibodies revealed that antigenic reactivity of E-domain I may be impacted by both residues E-152 and E-156. In conclusion, we proposed a role for the residues E-152/156/158 as key antigenic determinants of ZIKV glycan loop region.